2018
DOI: 10.1017/s1751731117002038
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition during the rearing phase for replacement ewes of four genotypes: I – effects on growth and development, and on ovulation rate at first joining

Abstract: Plane of nutrition (PN) offered to ewe replacements during the rearing phase (8 to 17 months) affects BW at joining and may affect reproductive performance when joined at ~19 months. The effects of PN offered to ewe replacements during their first winter (winter_1) and second summer (summer_2) were evaluated over 3 consecutive years, using 287 spring-born ewe lambs, representing four genotypes (Belclare (Bel), Charmoise×Scottish Blackface (C×SBF), Bel×SBF (Bel×SBF), Bel×SBF that were heterozygous either FecGH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Keady and Hanrahan [ 2 ] used the probability of rearing ≥ 1 lamb as an overall efficiency index since this encompassed ewe fertility and litter size together with ewe and lamb mortality. In the current study, the lack of an effect of BW at joining on the probability of rearing ≥ 1 lamb was expected, as earlier studies had shown that an 8.4 kg difference in BW when joined at 19 months did not affect ovulation rate, litter size or the number of lambs reared per ewe joined [ 8 , 9 ]. No published information was found on the effect of weight at 7 months on the productivity when joined to lamb at 2 years.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Keady and Hanrahan [ 2 ] used the probability of rearing ≥ 1 lamb as an overall efficiency index since this encompassed ewe fertility and litter size together with ewe and lamb mortality. In the current study, the lack of an effect of BW at joining on the probability of rearing ≥ 1 lamb was expected, as earlier studies had shown that an 8.4 kg difference in BW when joined at 19 months did not affect ovulation rate, litter size or the number of lambs reared per ewe joined [ 8 , 9 ]. No published information was found on the effect of weight at 7 months on the productivity when joined to lamb at 2 years.…”
Section: Discussionmentioning
confidence: 62%
“…Ewe body condition score (BCS) [ 23 ] was recorded pre joining, post joining, at lambing, at approximately week 5 post lambing, and at weaning. Withers height, body length, chest (heart) girth and circumference of the cannon bone were recorded for all ewes post mating (early November), as described previously [ 8 ]. This collection of linear measurements will be referred to as body size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation